Avaliação da técnica de duplo maçarico para ajuste do dimensionamento de placas de aço - Fabrício Domith Rodrigues (2019)
On Rolling Mills whose vertical rolling technology is non-existent or limited, eventually is necessary to adjust the width of the slabs by flame cutting process. However, the conventional flame cutting process is not recommended for some grades of steels due to generation of susceptibility to cracks in the cutting section. Thus, in the present work, a new technique for dimensional adjustment of slabs based on the use of double flame cut was developed and applied at Usiminas. After optimization of cutting parameters (velocity and position of the torches), temperatures of 200°C were obtained, homogeneously distributed along the cutting section, favoring dimensional adjustment. With the industrial implementation, there were indexes above 85% of slabs approval and, consequently, the use of plates that were not previously intended for the generation of rolling mill products. Keywords: Flame cutting, double torches and Slabs.